[125 I]IodoDPA-713 Binding to 18 kDa Translocator Protein (TSPO) in a Mouse Model of Intracerebral Hemorrhage: Implications for Neuroimaging - Bonsack, Frederick; Foss, Catherine A.; Arbab, Ali S.; Alleyne, Cargill H.; Pomper, Martin G.; Sukumari-Ramesh, Sangeetha (Frontiers in Neuroscience, 2018)
ICH is a fatal stroke subtype with significant public health impact. Although neuroinflammation is a leading cause of neurological deficits after ICH, no imaging tool is currently available to monitor brain inflammation in ICH patients. Given the role of TSPO in neuroinflammation, herein we investigate whether a second-generation TSPO ligand, [125 I]IodoDPA-713 can be used to monitor the changes in TSPO expression in a preclinical model of intracerebral hemorrhage. Male CD1 mice were subjected to ICH/Sham. The brain sections, collected at different time points were incubated with [125 I]IodoDPA-713 and the brain uptake of [125 I]IodoDPA-713 was estimated using autoradiography. The specificity of [125 I]IodoDPA-713 binding was confirmed by a competitive displacement study with an unlabeled TSPO ligand, PK11195. [125 I]IodoDPA-713 binding was higher in the ipsilateral striatum with an enhanced binding observed in the peri-hematomal brain region after ICH, whereas the brain sections from sham as well as contralateral brain areas of ICH exhibited marginal binding of [125 I]IodoDPA-713. PK11195 completely reversed the [125 I] IodoDPA-713 binding to brain sections suggesting a specific TSPO-dependent binding of [125 I]IodoDPA-713 after ICH. This was further confirmed with immunohistochemistry analysis of adjacent sections, which revealed a remarkable expression of TSPO in the areas of high [125 I]IodoDPA-713 binding after ICH. The specific as well as enhanced binding of [125 I]IodoDPA-713 to the ipsilateral brain areas after ICH as assessed by autoradiography analysis provides a strong rationale for testing the applicability of [125 I]IodoDPA-713 for non-invasive neuroimaging in preclinical models of ICH.